PENGASINGAN WANITA MELAHIRKAN SUKU NUAULU DI DUSUN ROHUA KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Sri Eny Setyowati (Poltekkes Kemenkes Semarang, 2016)
The aim of the research is to analyze the impact of a Knowledge in practicing of pregnancy in seclusion in Nuaulu’s tribe Two research methods are applied: qualitative and quantitative approach. Questioner method was used to collecting the data. Sixty-eight respondents participated in this research as a sample of Nuaulu’s mothers with under 3-year-old child. Nualu’s society lacks of knowledge about the practice of pregnancy in a good manner. For instance, they believe that a pregnant woman is possessed by demons and considerably danger in society. In addition, there is a relation between the Knowledge and The practice of pregnancy in seclusion. The probability of doing improper practice of pregnancy is 18,377 time higher if the respondents have little knowledge, compare with the ones who have good knowledge. Finaly, it is suggested that KIE (Communication, Information, and Education) for Nuaulu's woman and leaders can increases their knowledge about decent practice of pregnancy.